Challenges and Perception on Purchase Intention of EVs in Indonesian Distribution Logistics - Karen Karen; Deshiva Marolita Gultom; Tenaka Budiman; Novi Indah Susanthi (Jurnal Ilmu Multidisiplin, 2025)
In the context of green logistics, the adoption of electric vehicles (EVs) to replace conventional vehicles is considered a strategic step to reduce greenhouse gas emissions. However, distribution actors are faced with challenges and perceptions of electric vehicles that can affect their purchase intentions. This study aims to analyze the indicators of these challenges and perceptions of purchase intention. Data was collected through a quantitative approach by distributing a survey to 100 operational logistics distributors in Indonesia and processed using SmartPLS 3 to draw conclusions. The study concludes that while challenges in adopting EV do not significantly impact EV purchase intention, positive perceptions of EVs account for 48.9% of the influence, with other factors contributing the remaining 51.1%. The results provide insights into the challenges and perceptions of distributors towards EVs, offering valuable reference material for stakeholders to develop solutions and support the implementation of sustainable logistics.